The Tell-Tale Hand: Gothic Narratives and the Brain - Forsyth, Neil (Text Matters: A Journal of Literature, Theory and Culture, 2016)
The opening story in Winesburg, Ohio (1919) by Sherwood Anderson is called simply “Hands.” It is about a teacher’s remarkable hands that sometimes seem to move independently of his will. This essay explores some of the relevant contexts and potential links, beginning with other representations of teachers’ hands, such as Caravaggio’s St. Matthew and the Angel, early efforts to establish a sign-language for the deaf, and including the Montessori method of teaching children to read and write by tracing the shape of letters with their hands on rough emery paper. The essay then explores filmic hands that betray or work independently of conscious intentions, from Dr Strangelove, Mad Love, to The Beast With Five Fingers. Discussion of the medical literature about the “double” of our hands in the brain, including “phantom hands,” leads on to a series of images that register Rodin’s lifelong fascination with sculpting separate hands.